Divided in a digital economy: Understanding disability employment inequities stemming from the application of advanced workplace technologies - Arif Jetha; Silvia Bonaccio; Ali Shamaee; Cristina G. Banks; Ute Bültmann; Peter M Smith; Emile Tompa; Lori B Tucker; Cameron Norman; Monique A.M. Gignac (Elsevier, 2023)
Objectives: The digital transformation of the economy is characterized by the rapid advancement and wide-spread workplace application of digital technologies. Our study aimed to unpack how the digital transformation of the economy contributes to challenges and opportunities for the sustainable employment and health of persons living with disabilities. Methods: One-on-one semi-structured interviews with policy makers, disability employment service providers and future of work specialists were conducted. Interviewees asked about the implications of digital technology advancements for persons with disabilities. Participants were also asked about the strategies that could be used to support inclusive employment within a digitized working world. An iterative and flexible grounded theory methodological approach was taken to analyze the qualitative data and to develop a conceptual understanding of the digital transformation of the economy for persons living with disabilities. Results: Forty participants were interviewed from across Canada. The digital transformation of the economy was seen as disadvantageous to persons living with disabilities and could impact their ability to find and sustain paid work, advance within their career, and remain productive. Labelled as the digital divide, participants frequently referred to sources of inequities faced by persons with disabilities that shaped their ability to fully participate in a digital working world. The digital divide was characterized by three intersecting concepts which included disparities in digital technology access, personal resources, and job skills. Participants highlighted the importance of equity and inclusive design considerations in the development and dissemination of digital technology and more responsive skilling initiatives for a changing work environment. Conclusions: Findings provide an important conceptual foundation for scholarship on work and health inequities that can arise from the digital transformation of the economy and bring greater attention to the design of targeted disability employment support programs and policies that are relevant and inclusive for a digital working world.